KODE ETIK GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI INDONESIA - Lubis, Makmur; Ginting, Rahmadani Fitri (Cahaya Ilmu Bangsa Institute, 2024)
“This study aims to analyze the code of ethics and professionalism of teachers in improving the quality of education in Indonesia. The method used is qualitative descriptive analysis with a library research approach. The results show that teachers play a crucial role in shaping students' potential through talent development. There are four competencies that teachers must possess to enhance educational quality: pedagogical, personal, social, and professional competencies. The teacher's code of ethics emphasizes a commitment to improving educational quality, faith, piety, and noble character. Teachers who meet academic qualifications and possess good competencies have professional responsibilities and legal protection guarantees. However, the challenges faced by teachers today include rapid developments in information technology and the dynamics of decentralization and centralization in education. This study is expected to provide insights for educational policy development and the enhancement of teacher professionalism in Indonesia.”. Penelitian ini bertujuan untuk menganalisis kode etik dan profesionalisme guru dalam upaya meningkatkan mutu pendidikan di Indonesia. Metode yang digunakan adalah analisis deskriptif kualitatif dengan pendekatan library research. Hasil penelitian menunjukkan bahwa guru memiliki peran krusial dalam membentuk potensi siswa melalui pengembangan bakat. Terdapat empat kompetensi yang harus dimiliki guru untuk meningkatkan mutu pendidikan, yaitu kompetensi pedagogik, personal, sosial, dan profesional. Kode etik guru menekankan komitmen terhadap peningkatan mutu pendidikan, keimanan, ketakwaan, dan akhlak mulia. Guru yang memenuhi kualifikasi akademik dan kompetensi yang baik memiliki tanggung jawab profesional serta jaminan perlindungan hukum. Namun, tantangan yang dihadapi guru saat ini mencakup perkembangan teknologi informasi yang pesat dan dinamika desentralisasi serta sentralisasi pendidikan. Penelitian ini diharapkan dapat memberikan wawasan bagi pengembangan kebijakan pendidikan dan peningkatan profesionalisme guru di Indonesia.